Compressive Strength, Chloride Permeability, and Freeze-Thaw Resistance of MWNT Concretes under Different Chemical Treatments - Xingang Wang; Inkyu Rhee; Yao Wang; Yunping Xi (The Scientific World Journal)
This study investigated compressive strength, chloride penetration, and freeze-thaw resistance of multiwalled carbon nanotube (MWNT) concrete. More than 100 cylindrical specimens were used to assess test variables during sensitivity observations, including water-cement ratios (0.75, 0.5, and 0.4) and exposure to chemical agents (including gum arabic, propanol, ethanol, sodium polyacrylate, methylcellulose, sodium dodecyl sulfate, and silane). To determine the adequate sonication time for MWNT dispersal in water, the compressive strengths of MWNT concrete cylinders were measured after sonication times ranging from 2 to 24 minutes. The results demonstrated that the addition of MWNT can increase the compressive strength of concrete by up to 108%. However, without chemical treatment, MWNT concretes tend to have poor freeze-thaw resistance. Among the different chemical treatments, MWNT concrete treated with sodium polyacrylate has the best compressive strength, chloride resistance, and freeze-thaw durability.